Tekat as a Malaysian heritage: a study of motif, form and meaning / Saemah Yusof - Yusof, Saemah (2014)
Tekat is a form of embroidery on cloth, usually velvet, using gold threads whereby shapes and patterns are formed by stitching the gold threads over a core of medium-thickness pre-cut papers (mempulur). It is one of the traditional handicrafts that have been handed down the generations. Today, this Malay art of embroidery still lives on but only in a few locations. Almost all practitioners of tekat tuji are to be found in the royal town of Kuala Kangsar, Perak. Even so, their days are numbered as many are old and often have no heirs to their knowledge. Hence, the art of tekat is facing severe decline if not total extinction. Several reasons are attributed to this phenomenon. Firstly, is the lack of practitioners of tekat. The second reason is that very few of the younger generation are involved in tekat art. Thirdly, the products of tekat are not commercial enough. If nothing is done to arrest this decline, the art will only be relegated to only a few treasured pieces kept by the museums or collectors. As such, this study is intended to document the art of tekat as a means to continue and preserve this art before its demise. Three hypotheses are forwarded in this study. The first hypothesis is that describing and documenting all aspects of the art of tekat can help to preserve and perpetuate it for the future generation. The second hypothesis claims that new tekat products can be created so as to make them more commercial and practical for daily uses. The third hypothesis is that the art of tekat can attract fresh interest among the younger generation especially, if it is often introduced and widely promoted to the public. The methodology used is a qualitative descriptive research using interviews as the instrument. Eleven respondents comprising of tekat makers, academicians, authors and government officials were selected. The data collected was analysed using “Content Analysis”. In addition, a Formalistic Study was also conducted on selected samples of motifs. The overall findings showed that tekat is indeed in dire straits and facing extinction in the near future. Nevertheless, the researcher felt there is still hope for it and had made several recommendations to preserve and perpetuate this art form.